2012
DOI: 10.1371/journal.pone.0046767
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Trypanosoma cruzi Trypomastigotes to Fibronectin or Laminin Modifies Tubulin and Paraflagellar Rod Protein Phosphorylation

Abstract: BackgroundThe unicellular parasite Trypanosoma cruzi is the causative agent of Chagaś disease in humans. Adherence of the infective stage to elements of the extracellular matrix (ECM), as laminin and fibronectin, is an essential step in host cell invasion. Although members of the gp85/TS, as Tc85, were identified as laminin and fibronectin ligands, the signaling events triggered on the parasite upon binding to these molecules are largely unexplored.Methodology/Principal FindingsViable infective parasites were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 59 publications
1
20
0
3
Order By: Relevance
“…Earlier studies showed that activation of transforming growth factor‐β (TGF‐β) receptor enhances T. cruzi entry into cardiomyocyte and other cell types (Ming et al ., ; Waghabi et al ., 2005; 2007), as does binding to kinin receptors (Todorov et al ., ). Although our results suggest that PDNF family member gp85 does not initiate a cascade of events triggering TrkC‐dependent cardiomyocyte invasion, independent studies showed that gp85 is important in T. cruzi adhesion to laminin and other ECM components (Alves and Colli, ; Mattos et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies showed that activation of transforming growth factor‐β (TGF‐β) receptor enhances T. cruzi entry into cardiomyocyte and other cell types (Ming et al ., ; Waghabi et al ., 2005; 2007), as does binding to kinin receptors (Todorov et al ., ). Although our results suggest that PDNF family member gp85 does not initiate a cascade of events triggering TrkC‐dependent cardiomyocyte invasion, independent studies showed that gp85 is important in T. cruzi adhesion to laminin and other ECM components (Alves and Colli, ; Mattos et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…cruzi contain homologues of the MAP kinase ERK and the peptidyl-prolyl cis/trans isomerase (PPIase) PIN1 which in the human tumour cells are involved in the signalling resulting in translocation of PGK1 to mitochondria and exhibiting protein kinase activity [156][157][158][159]. The T. brucei and T. cruzi ERK homologues are called Erk-like (TbECK1) and Erk2 (TcMAPK2), respectively [156,157]. These proteins are associated with functions related to phenotype, karyotype, cell cycle and growth modulation.…”
Section: Does Pas-pgk-like Protein Act As a Protein Kinase?mentioning
confidence: 99%
“…Adhesion to laminin or fibronectin leads to changes in the phosphorylation level of T . cruzi proteins, including paraflagellar rod proteins and tubulins, probably involving the ERK1/2 pathway [ 50 ].…”
Section: Introductionmentioning
confidence: 99%